Utilization of Beliefs and Food Taboos in The ’Horse-Man’ Myth as BIPA Learning Content in East-Timor - Elisabeth Merniana Bera; Nuny Sulistiany Idris; Suci Sundusiah (Jurusan Tadris Bahasa Indonesia, 2025)
This research analyzes the